Pengembangan Profesional Pendidik PAI - Yulisa Dwi Astuti; Fadriati; Ermis Suryana (Jurnal Pendidikan dan Humaniora Rumbio, 2024)
The mode used in this article is descriptive type research with library research. Where the results of the discussion of this article are the development of teacher professionalism including aspects of pedagogical competence, content knowledge, educational technology skills, social and emotional abilities and sustainable learning. To create professional teachers, the right strategy is needed, namely: training and workshops, communities of practice, mentoring and coaching, use of technology collaboration and partnerships.